2017 Ieee Sensors 2017
DOI: 10.1109/icsens.2017.8234206
|View full text |Cite
|
Sign up to set email alerts
|

Portable, in-field, multispectral imaging sensor for real-time detection of insect viral-vectors

Abstract: -The paper introduces a multispectral imaging system and data-processing approach for speciation of the insect viral vectors (whitefly) responsible for the transmission of Mosaic and Brown Streak viruses in Sub-Saharan African cassava. The trial results for four species of whitefly, on two plant leaf types (cassava & aubergine), are reported as well as the methodology applied. This indicates that a correct classification could be achieved in 85-95% of cases. The engineering design for an infield, handheld, var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Red scales were the smallest insects on the traps as the spatial evaluation performed through the camera attached to the microscope later confirmed. From the literature, it was found that the red scale is the smallest insect along with the whiteflies (1mm -2 mm length) studied by Grieve et al [11], which had a green appearance, very different from red scales. The other insects were bigger, even with a size of some centimeters.…”
Section: Morphological Featuresmentioning
confidence: 96%
See 2 more Smart Citations
“…Red scales were the smallest insects on the traps as the spatial evaluation performed through the camera attached to the microscope later confirmed. From the literature, it was found that the red scale is the smallest insect along with the whiteflies (1mm -2 mm length) studied by Grieve et al [11], which had a green appearance, very different from red scales. The other insects were bigger, even with a size of some centimeters.…”
Section: Morphological Featuresmentioning
confidence: 96%
“…However, the high cost of NIR image sensors promoted the use of other spectral ranges such as the VIS and the ultraviolet (UV) when deploying multispectral imaging (MSI) systems [11,12]. To reduce the cost, smaller sensors in size are selected in the NIR, providing lower spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation